Political history of Spain (2016–2020): overcoming the crisis - N. E. Anikeeva (Ибероамериканские тетради)
In this article the author analyses the development of political process in Spain between the two crises of 2015–2016 and 2019–2020, highlighting the strong suits and problem issues of the domestic political debate, including the Catalan issue, as well as the problem related to the migration aspect. An overview of the evolution of the country’s foreign policy agenda is presented, including the foreign policy course towards the Russian Federation. The author analyzes political and economic aspects after the general parliamentary elections of June 26, 2016, which resulted in overcoming the governmental crisis that began in Spain in December 2015 and establishing Mariano Rajoy the head of the Popular Party (PP) government. The latest cabinet of the PP government was approved in November 2016. Rajoy himself had been serving as a Prime Minister of Spain from December 2011 to June 2018. Soon, a new stage in the political history of the Spanish state began, which was associated with the rise to power of the Spanish Socialist Workers Party (PSOE) led by Pedro Sánchez since 2018. PSOE thus won the parliamentary elections in Spain on April 28, 2019. The next elections in 2019 were held on November 10 and turned out to be much more complex and unpredictable than the previous one. PSOE stroke a similar political balance of power to that of April. Confirmation of Pedro Sánchez as a Prime Minister of Spain in January 2020 ended a protracted political crisis in the country, when the Spanish government had been in an acting status for some eight months.